Resistance and reproduction: an arts-based investigation into young people’s emotional responses to crime - Dodsley, Thomas (The British journal of criminology, 2021)
This paper reports on a qualitative study of young people’s emotional responses to crime, underpinned by cultural criminology and interpretive phenomenology. It uses alternative approaches to explore young people’s ‘fears’ of crime via the use of arts-based methods, specifically performative drama and focus groups. The rationale is rooted in young people’s voices being largely absent from fear of crime research and the increased movement towards a more creative and less prescriptive criminology. The findings point towards the value of such approaches and argue that young people’s emotions about crime become highly gendered and age-relevant in youth and have multiple, overlapping spheres that are culturally constructed, resisted and reproduced.